2011
DOI: 10.1016/j.anorl.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Should older head and neck patients be treated differently?

Abstract: HNSCC is a serious disease that often necessitates aggressive treatment. All patients who are medically eligible should receive curative treatment, without age being an exclusion criterion. Taking comorbidity into account, on the other hand, enables treatment options to be optimized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…[21][22][23][24]30 They also suggest that, while the benefits of chemotherapy are similar in the fit elderly compared to younger patients, the toxicities of chemotherapy, both used alone and combined with other modalities, may be greater. Researchers are still working on a good definition of "fit elderly" in order to define this favorable population.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[21][22][23][24]30 They also suggest that, while the benefits of chemotherapy are similar in the fit elderly compared to younger patients, the toxicities of chemotherapy, both used alone and combined with other modalities, may be greater. Researchers are still working on a good definition of "fit elderly" in order to define this favorable population.…”
Section: Resultsmentioning
confidence: 95%
“…20 Aside from this influence of comorbidities, several studies have demonstrated that surgical treatment of head and neck cancer can in fact be safely performed in the older population without an increase in the risk of postoperative complications or death when compared to the younger population. [21][22][23][24] Even if surgical therapy can be safely performed for head and neck cancer in the elderly, is it worthwhile? The answer seems to be affirmative.…”
Section: Surgerymentioning
confidence: 98%
“…The conventional fractionated RT regimens usually last from 4 to 6 weeks. However, some elderly patients, or those from rural locations, cannot tolerate prolonged RT schedules, and an accelerated hypofractionated schedule has been used to shorten the overall treatment time without compromising therapeutic outcomes . Given the lack of data on radiation regimens suitable for elderly patients, we decided to assess the effectiveness of different RT regimens for NMSC in the head and neck.…”
Section: Introductionmentioning
confidence: 99%
“…However, the cosmetic outcome depends on the cancer location. 5,6 An accelerated hypofractionated schedule is often selected to shorten the treatment time for patient convenience and the conventional wisdom that they might not tolerate a prolonged treatment course. 3 In addition, patients with multiple comorbidities are often excluded from surgery because of the risk of complications.…”
Section: Introductionmentioning
confidence: 99%
“…4 Thus, elderly cancer patients are often referred for radiotherapy only because of the perception that they might not tolerate surgery. 5,6 An accelerated hypofractionated schedule is often selected to shorten the treatment time for patient convenience and the conventional wisdom that they might not tolerate a prolonged treatment course. [7][8][9] Although excellent local control is undeniable (95-98% at 5 years), a large dose per fraction could lead to late soft tissue necrosis if the dose exceeds 10 Gy a day.…”
Section: Introductionmentioning
confidence: 99%